Introduction to black holes, information and the string theory revolution:the holographic universe - Susskind, Leonard; Lindesay, James (New Jersey, World Scientific Publishing Co. Pvt.. Ltd., 2005)
Over the last decade the physics of black holes has been revolutionized by developments that grew out of Jacob Bekenstein's realization that black holes have entropy. Stephen Hawking raised profound issues concerning the loss of information in black hole evaporation and the consistency of quantum mechanics in a world with gravity. For two decades these questions puzzled theoretical physicists and eventually led to a revolution in the way we think about space, time, matter and information. This revolution has culminated in a remarkable principle called (3z(BThe Holographic Principle(3y(B, which is now a major focus of attention in gravitational research, quantum field theory and elementary particle physics. Leonard Susskind, one of the co-inventors of the Holographic Principle as well as one of the founders of String theory, develops and explains these concepts.s
Bibliography p179; Index 181-183p.
Keywords: Astronomy; Black holes; String theory; Mathematics